2011
DOI: 10.1128/aem.02427-10
|View full text |Cite
|
Sign up to set email alerts
|

Decay of Bacterial Pathogens, Fecal Indicators, and Real-Time Quantitative PCR Genetic Markers in Manure-Amended Soils

Abstract: This study examined persistence and decay of bacterial pathogens, fecal indicator bacteria (FIB), and emerging real-time quantitative PCR (qPCR) genetic markers for rapid detection of fecal pollution in manureamended agricultural soils. Known concentrations of transformed green fluorescent protein-expressing Escherichia coli O157:H7/pZs and red fluorescent protein-expressing Salmonella enterica serovar Typhimurium/pDs were added to laboratory-scale manure-amended soil microcosms with moisture contents of 60% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 61 publications
9
83
1
Order By: Relevance
“…It has been found that both E. coli and enterococci can survive in the soil for several weeks after deposition, if not longer (7,8). Some studies have found that populations of these organisms can experience initial growth in the soil that can extend their prevalence for longer than previously thought.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It has been found that both E. coli and enterococci can survive in the soil for several weeks after deposition, if not longer (7,8). Some studies have found that populations of these organisms can experience initial growth in the soil that can extend their prevalence for longer than previously thought.…”
mentioning
confidence: 92%
“…Contamination of soil and water leading to foodborne illness can originate from numerous sources, such as direct deposition by animals, overflow or leakage of faulty septic and sewage systems, or manure application to agricultural fields and pastures (3-5). The potential presence of pathogens that cause foodborne illness can be inferred via the monitoring of fecal indicator bacteria (FIB), such as Escherichia coli and enterococci (6).It has been found that both E. coli and enterococci can survive in the soil for several weeks after deposition, if not longer (7,8). Some studies have found that populations of these organisms can experience initial growth in the soil that can extend their prevalence for longer than previously thought.…”
mentioning
confidence: 99%
“…In addition to pathogens, PM commonly contains nonpathogenic bacteria, including Escherichia coli (EC) and enterococci (ENT) (Terzich et al, 2000;Rogers et al, 2011). Studies of human exposures have confirmed the increased risk of negative health outcomes from swimming in waters containing these and other fecal indicator bacteria (FIB) (Pruss, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of PMamended soils have reported survival of FIB and pathogens for weeks and months after application (Rogers et al, 2011;Cook et al, 2014), highlighting the potential for continued release of bacteria to subsurface waters.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of Gompertz models to predict microbial populations under different temperatures has made them versatile for modelling purposes. The broken‐line model (Carrera et al ., 2007; Rogers et al ., 2011) was used to account for abrupt changes in the non‐linearity in inactivation curve. Points of abrupt changes known as ‘break points’ were developed originally to provide a better understanding of the kinetic parameters at different points of departure in the inactivation curve.…”
Section: Introductionmentioning
confidence: 99%